Modelling of dynamic characteristics of tractor systems to improve stability on uneven fields - V. Duhanets; P. Fedirko; O. Hovorov; V. Pukas; M. Volynkin (Machinery & Energetics, 2025)
The study aimed to determine the impact of the centre of mass shift, the angle of inclination of the terrain and local disturbances on the spatial stability of the transport system, with the subsequent determination of its equilibrium limit modes. The methodology was based on a combination of theoretical modelling, adaptive control and multi-level validation in a changing environment. The critical vertical displacement of the hull was found to be up to 0.15 m at an 18° tilt due to the asymmetric passage of obstacles, which confirmed the need for accurate dynamics prediction. Stability analysis has established safe roll angles of 25-30° for Ukrainian black soil (friction coefficient 0.6-0.8). The uneven load and soil moisture content (20-30%) affected stability, requiring model calibration. Hybrid methods compensated for seat vibrations by adaptively controlling the damper. Adaptive ground contact improved traction on soft ground, while nonlinear predictive steering optimised the trajectory on slopes. The expediency of the geometry of the reference plane and the position of the centre of mass when developing algorithms for stabilising agricultural machinery, given the impact on stability in variable terrain, was established. Stochastic modelling of soil disturbances was used to predict the impact of random environmental changes on the trajectory and stability of the equipment. The proposed theoretical model is suitable for the design and dynamic hull control systems, especially for operation on slopes and complex geometries. The integration of sensor systems with models ensured adaptation to real-time conditions. The practical value of the results was to improve the safety of agricultural machinery and optimise its spatial orientation on slopes by process engineers and developers of active levelling systems when designing new generation machinery